On Moore's Notion of Proof. Issue 3 (30th April 2020) - De, Michael
Abstract: Much has been said about Moore's proof of the external world, but the notion of proof that Moore employs has been largely overlooked. I suspect that most have either found nothing wrong with it, or they have thought it somehow irrelevant to whether the proof serves its antiskeptical purpose. I show, however, that Moore's notion of proof is highly problematic. For instance, it trivializes in the sense that any known proposition is provable. This undermines Moore's proof as he conceives it since it introduces a skeptical regress that he goes at length to resist. I go on to consider various revisions of Moore's notion of proof and finally settle on one that I think is adequate for Moore's purposes and faithful to what he says concerning immediate knowledge.